Prediction of the Development of Acute Heart Failure of High Grades in Patients with Myocardial Infarction and Percutaneous Coronary Intervention - Andrii V. Solomonchuk; Lesia V. Rasputina; Daria V. Didenko (Ukrainian Journal of Cardiovascular Surgery, 2023)
The aim of the study was to determine the risk factors for the occurrence of acute heart failure (AHF) of high degrees (Killip classes III and IV) among patients with myocardial infarction (MI).Materials and methods. We examined 308 MI patients who were treated at the specialized cardiology department. The mean age of the subjects was 62.9±0.6 years. There were 161 (52.3%) patients with MI without signs of heart failure (HF) (Killip class I), 44 (14.3%) with MI combined with class II AHF, 55 (17.8%) with MI and class III AHF, and 48 (15.6%) with MI and Killip class IV AHF. In addition to the general clinical examination, all the patients underwent additional laboratory examination (quantitative determination of troponin I, D-dimer, creatine kinase-MB, C-reactive protein, N-terminal prohormone of brain natriuretic peptide [NT-proBNP]), echocardiography and lung ultrasound during hospitalization, as well as coronary angiography.Results. A correlation between the occurrence of class III AHF (pulmonary edema) and class IV AHF (cardiogenic shock) and a number of anamnestic, clinical, functional and laboratory indicators was established. The following predictors of the development of class III AHF among patients with MI were calculated through regression analysis: a decrease in the level of O2 saturation during hospitalization, an increase in blood pressure during hospitalization, localization of the main heart attack-related lesion of the distal part of the right coronary artery, a decrease in the left ventricular ejection fraction. With less significance, predictors of the development of class III AHF were also defined as a decrease in the level of hemoglobin, the duration of hypertension in the history, the degree of hypertension, the history of any form of atrial fibrillation.Conclusions. A decrease in diastolic blood pressure irrespective of medical support and an increase in the level of NT-proBNP were established as predictors of the development of Killip class IV AHF. Further studies to predict the occurrence of HF and long-term consequences after MI with high-grade HF are promising and can provide an opportunity to optimize the treatment of patients by preventing severe complications.